Natural Disasters as a Maternal Prenatal Stressor and Children’s Neurodevelopment: A Systematic Review - Gül Ünsel-Bolat; Sema Yıldırım; Fethiye Kılıçaslan; Rafael A. Caparros-Gonzalez (Behavioral Sciences)
The intrauterine period is a time of high sensitivity in the development of the embryo and the fetus. Therefore, low levels of maternal stress are closely associated with healthy brain development in the neonatal and early childhood periods. There is increasing evidence linking natural disasters as prenatal maternal stress (PNMS) to neurodevelopmental disorders (including subclinical manifestations). Natural disasters involve many factors in addition to the trauma they cause, including loss and the physical and psychosocial difficulties that result from that trauma. This review article aims to bring together research findings on the neurodevelopmental effects of natural disasters on children as PNMS. It also looks at how factors such as gestational age and gender contribute to these effects. We conducted a systematic review on PubMed, Web of Science, and Scopus, with 30 studies meting the inclusion criteria. This systematic review was conducted in accordance with the PRISMA guidelines. A total of 1,327,886 mother–child dyads participated in the included studies. The results of the studies indicate that natural disasters have a negative impact on children’s outcomes in terms of cognitive development, language development, autism/autism-like features, motor skills, performance in mathematics, mental development, sleep, attention, behavioral and emotional problems, and various psychiatric comorbidities.